Anteseden dan Konsekuensi Pengelolaan Keuangan UMKM di Kota Jayapura - Randa Layuk, Selvi Yanti; Pangayow, Bill J. C.; Matani, Cornelia D.; Siahay, Adolf Z. D; Bleskadit, Novalia H.; Salle, Hesty Theresia (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2025)
This research is a quantitative study which aims to examine the Antecedents and Consequences of MSME Financial Management in Jayapura City. This research used a sample of 99 respondents who were MSMEs in Jayapura City. The data analysis technique used in this research is analysis with the Structural Equation Modeling (SEM) model that will be used in this research is Partial Least Square (PLS) which consists of 2 stages of testing the PLS Measurement Model, namely the Structural Model and the Measurement Model. The tools used are SmartPLS 4.0 and SPSS programs. The test results obtained in this research are: (1) financial inclusion has a significant and positive effect on the financial management of MSMEs in Jayapura City; (2) financial literacy has a significant and positive effect on the financial management of MSMEs in Jayapura City; (3) financial management has a significant effect on the performance of MSMEs in Jayapura City; (4) financial inclusion has a significant and positive effect on the performance of MSMEs through financial management in Jayapura City; (5) financial literacy has a significant and positive effect on the performance of MSMEs through financial management in Jayapura City.Keywords: financial inclusion, financial literacy, msme performance, financial management